Computer Program for Optimizing Compounding of High-Octane Gasoline; Chemistry and Technology of Fuels and Oils; Vol. 50, iss. 1 - Kirgina M. V. Mariya Vladimirovna; Ivanchina E. D. Emilia Dmitrievna; Dolganov I. M. Igor Mikhailovich; Chekantsev N. V. Nikita Vitalievich; Kravtsov A. V. Anatoly Vasilyevich; Фу Фан (2014, 2014)
Title screen